IMPLEMENTASI FUNGSI MANAJEMEN DALAM PENERAPAN BOARDING SCHOOL - Alwi, Muhamad (El Banar : Jurnal Pendidikan dan Pengajaran, 2023)
The implementation of management functions in the implementation of boarding schools is very important to achieve the goals of national education and the goals of these educational organizations. Experts differ in formulating the management process, but in essence there are several similarities covering four management functions that must be considered, namely boarding school planning, boarding school organizing, boarding school implementation, and boarding school supervision. By paying attention to the four functions of education management above, it is expected to improve the overall quality of education. The method used in this research is library research. From the results of the literature research, it can be concluded that the implementation of a good boarding school management function can improve achievement and religious character of Ma'had Al-Qolam MAN 2 Malang City, improve the quality of education at MAN 1 Yogyakarta, improve the quality of education at SMA IT Abu Bakar Yogyakarta.